2001
DOI: 10.1104/pp.125.2.1012
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Intragenic Recombination Contributes to Allelic Diversity of the S-RNase Gene at the Self-Incompatibility (S) Locus in Petunia inflata  

Abstract: (T.T., T.A.)For Solanaceae type self-incompatibility, discrimination between self and nonself pollen by the pistil is controlled by the highly polymorphic S-RNase gene. To date, the mechanism generating the allelic diversity of this gene is largely unknown. Natural populations offer a good opportunity to address this question because they likely contain different alleles that share recent common progenitors. We identified 19 S haplotypes from a natural population of Petunia inflata in Argentina, used reverse t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 41 publications
4
58
1
Order By: Relevance
“…If coadaptation is primarily between amino acids in different parts of the molecule, linkage disequilibrium could extend across considerable distances, and a decline with distance would be undetectable unless only closely segregating sites are analysed. For P. inflata, both we and Schierup et al (2001) found only weak evidence for recombination, in disagreement with the results of Wang et al (2001). Highly divergent sequences in our data set, and that of Schierup et al (2001) might, however, obscure evidence for recombination.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…If coadaptation is primarily between amino acids in different parts of the molecule, linkage disequilibrium could extend across considerable distances, and a decline with distance would be undetectable unless only closely segregating sites are analysed. For P. inflata, both we and Schierup et al (2001) found only weak evidence for recombination, in disagreement with the results of Wang et al (2001). Highly divergent sequences in our data set, and that of Schierup et al (2001) might, however, obscure evidence for recombination.…”
Section: Resultscontrasting
confidence: 57%
“…However, some intragenic recombination at the S-locus has been inferred for several species of Solanaceae. S-locus sequence diversity is higher than at S-linked loci (unpublished results in McCubbin and Kao, 1999;Li et al, 2000) and inconsistent evolutionary histories were observed for the 5 0 and 3 0 regions of the S-locus in two sets of four closely related P. inflata S-alleles, suggesting recombination (Wang et al, 2001). Schierup et al (2001) used the informative sites test (Worobey, 2001) and r 2 test of recombination, and also found evidence for recombination in two species of Solanaceae, but not in P. inflata.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of recombination varies among the loci depending on the chromosomal location and sequence structure. Recombination can occur even within single genes, e.g., the S-RNase gene of INF (Wang et al 2001), the mutS gene of Salmonella enterica (Brown et al 2002), and the cinnamoyl CoA reductase gene of Eucalyptus (Poke et al 2006). The following evidence may support the assumption that interallelic recombination occurred between Hf1a and Hf1i to generate Hf1c in commercial petunias.…”
Section: Possible Cause and Conceivable Evidence Of Interallelic Recosupporting
confidence: 56%
“…For all alleles tested, we rejected the null hypothesis of full compatibility; thus, the S-RNase sequences isolated in this study represent unique specificities. Although allelic diversity in our sample is within the range reported for Solanaceae with GSI (Richman et al, 1995;Wang et al, 2001;Lu, 2002;Stone and Pierce, 2005;Savage and Miller, 2006), we recovered fewer alleles than are typically reported. For example, Igic et al, 2007 report 30 alleles from 34 individuals of the closely related species S. chilense, although several factors likely contribute to this discrepancy.…”
Section: Js Miller and Jl Kostyunmentioning
confidence: 74%